Tunnelling Mechanism in Noncommutative Space with Generalized Uncertainty Principle and Bohr-Like Black Hole - Sourav Haldar; Christian Corda; Subenoy Chakraborty (Advances in High Energy Physics)
The paper deals with nonthermal radiation spectrum by tunnelling mechanism with correction due to the generalized uncertainty principle (GUP) in the background of noncommutative geometry. Considering the reformulation of the tunnelling mechanism by Banerjee and Majhi, the Hawking radiation spectrum is evaluated through the density matrix for the outgoing modes. The GUP corrected effective temperature and the corresponding GUP corrected effective metric in noncommutative geometry are determined using Hawking’s periodicity arguments. Thus, we obtain further corrections to the nonstrictly thermal black hole (BH) radiation spectrum which give new final distributions. Then, we show that the GUP and the noncommutative geometry modify the Bohr-like BH recently discussed in a series of papers in the literature. In particular, we find the intriguing result that the famous law of Bekenstein on the area quantization is affected neither by noncommutative geometry nor by the GUP. This is a clear indication of the universality of Bekenstein’s result. In addition, we find that both the Bekenstein-Hawking entropy and the total BH entropy to third-order approximation are still functions of the BH quantum level.